Specialized Proresolving Mediators Facilitate the Immunomodulation of the Periodontal Ligament Stem Cells - Yu, Ning; Rakian, Audrey; Dean, Afsah; Van Dyke, Thomas E. (Frontiers in Dental Medicine, 2021)
Recent investigations into the regulation of the inflammation in the periodontitis have revealed that chronic inflammatory diseases such as periodontitis are characterized by an imbalance in the proinflammatory and proresolution mediators and can be characterized by a failure of the resolution pathways in the late stages of the acute inflammatory response. The proresolution mediators, termed as specialized proresolving mediators (SPMs), comprise the lipoxins, resolvins, protectins, and maresins that are derived from the arachidonic acid or omega-3 polyunsaturated fatty acids. In the animal studies, treatment of the periodontitis with the topical SPMs return the inflammatory lesion to the homeostasis with the regeneration of all the components of the periodontal organ lost to the disease. In this article, the study investigates the immunomodulatory role of SPMs in the periodontal ligament stem cells (PDLSCs). Primary porcine PDLSCs (pPDLSCs) were stimulated with interleukin-1β (IL-1β) and interleukin-17 (IL-17) in vitro to simulate the periodontal inflammation in the presence or absence of SPMs. This study found that IL-1β and IL-17 synergistically activated the proinflammatory genes of pPDLSCs and altered the immune phenotype of pPDLSCs including the key signaling pathways. Addition of SPMs rescued the pPDLSCs phenotype and induced further production of the additional SPMs, which was reflected by upregulation of the requisite enzymes 12- and 15-lipoxygenase by pPDLSCs. This study interrogated the immunomodulatory actions of pPDLSCs on the monocytes/macrophages, focusing on the porcine CD14/CD16/CD163 markers by using flow cytometry. This study utilized the CD14+CD16+/CD14+CD16− ratio and CD163 on the monocytes/macrophages to differentiate between a proinflammation phenotype (lower ratio) and a resolution of the inflammation phenotype (higher ratio). This study also found that the conditioned medium from pPDLSCs treated with the cytokines and Maresin1 increased the CD14+CD16+/CD14+CD16− ratio and had the highest CD163 expression. This study concludes that in an inflammatory environment, pPDLSCs become proinflammatory and exert immunomodulatory functions. Maresin 1 resolves the inflammation by acting on pPDLSCs directly and by shifting the monocytes/macrophages phenotype to the proresolution dominance.